2018
DOI: 10.1002/2017gl076058
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Irregularities and Acoustic/Gravity Wave Activity Above Low‐Latitude Thunderstorms

Abstract: Ionospheric irregularities due to plasma bubbles, scintillation, and acoustic/gravity waves are studied in the low‐latitude ionosphere in relation to thunderstorm activity. Ionospheric total electron content (TEC) measurements from the Low Latitude Ionospheric Sensor Network and lightning measurements from the World‐Wide Lightning Location Network are compared during two summer months and two winter months in 2013. Large amplitude fluctuations in TEC are found to have a strongly peaked diurnal pattern in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
3
13
1
1
Order By: Relevance
“…The diurnal variation of daytime ionospheric GW activity on LS days in this study area is different to that of South America in the southern hemisphere, as reported by Lay [24]. According to Lay [24], the diurnal variation pattern on LS days is similar to that on HS days, and the magnitude of the former is always smaller than that of the latter. These distinct results may be attributed to the different study areas and employed data.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…The diurnal variation of daytime ionospheric GW activity on LS days in this study area is different to that of South America in the southern hemisphere, as reported by Lay [24]. According to Lay [24], the diurnal variation pattern on LS days is similar to that on HS days, and the magnitude of the former is always smaller than that of the latter. These distinct results may be attributed to the different study areas and employed data.…”
Section: Discussioncontrasting
confidence: 50%
“…Ionospheric GW activity may show differences based on longitudinal differences between the southern region of China and South America, even though both are in low latitudes. In addition, only 11 days were used by Lay to calculate the diurnal averages of thunderstorm activity on LS days [24], while over 50 days in each year were used in this study (Table 1). Non-thunderstorm events during the 11 LS days in Lay's study [24] could have been unnoticeable, so the original variation pattern was preserved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations